2021
DOI: 10.1038/s41427-021-00308-w
|View full text |Cite
|
Sign up to set email alerts
|

Lead-halide Cs4PbBr6 single crystals for high-sensitivity radiation detection

Abstract: Low-dimensional perovskite materials and their derivatives with excellent optical performance are promising candidates for light-emission applications. Herein, centimeter lead-halide Cs4PbBr6 single crystals (SCs), which have been used for radiation detection with the indirect conversion method, were synthesized by a facile solution process. The Cs4PbBr6 scintillator exhibits bright green emission peaking at 525 nm and a high photoluminescence quantum yield (up to 86.7%) under 375 nm laser excitation. The Cs4P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 39 publications
4
45
0
Order By: Relevance
“…However, their properties such as fast decay times, narrow emission bands, and high light yield are also desirable for scintillation detectors. Some papers have been published on this topic [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ], but not nearly as many.…”
Section: Introductionmentioning
confidence: 99%
“…However, their properties such as fast decay times, narrow emission bands, and high light yield are also desirable for scintillation detectors. Some papers have been published on this topic [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ], but not nearly as many.…”
Section: Introductionmentioning
confidence: 99%
“…is employed to present the relationship between the mass attenuation coefficient of CsI, CsPbBr 3 , Cs 4 PbBr 6 , Bi 4 Ge 3 O 12 (BGO), and the photon energy of X-ray, which was obtained from the XCOM database. 22 To further explore the stability of the Cs 4 PbBr 6 glass ceramic under long-time Xray irradiation, a series of contrast experiments were carried out. The Cs 4 PbBr 6 glass ceramic samples (15 days) were irradiated under 50 keV X-rays for different times, and their RL luminescence was also recorded in RL spectra.…”
Section: Resultsmentioning
confidence: 99%
“…9,20,21 For example, Ouyang's team synthesized centimeter-sized lead-halide Cs 4 PbBr 6 single crystals by solution processing and found that Cs 4 PbBr 6 single crystals exhibited not only a high photoluminescence quantum yield (PLQY) but also strong green emission under X-ray excitation. 22 In 2019, CsPbBr 3 @ Cs 4 PbBr 6 powder was synthesized via a recrystallization method by Zeng's team, and a large-area CsPbBr 3 @Cs 4 PbBr 6 film (360 mm × 240 mm) fabricated by a blade-coating technique imaging screen showed high-quality X-ray imaging. 21 However, to date, most of the reported scintillator materials based on halide perovskites are all prepared from the single crystal or powder with high crystallinity, but the stability under long-term X-ray irradiation still needs to be further improved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As scintillator materials, perovskites effectively absorb light in a wide range from the ultraviolet to the visible and near-infrared region [7] and yield light of various wavelengths. In previous works [8,9], the absorption efficiency of lead halide perovskites for 250 nm to 450 nm light was over 97%. The wavelengths of the output light were 90% concentrated in the range from 500 nm to 570 nm.…”
Section: Introductionmentioning
confidence: 93%